Pengaruh Penambahan Inulin terhadap Mutu Sensorik, Kandungan Serat dan Daya Terima Yoghurt - Fikriyah, Hanifah; Habibi, Nur Ahmad; Ismanilda, Ismanilda; Darningsih, Sri; Zulkifli, Zulkifli; Andrafikar, Andrafikar; Edmon, Edmon (Poltekkes Kemenkes Padang, 2024)
Yogurt is a functional food that contains probiotic bacteria beneficial for health. The addition of inulin fiber is considered to increase the fiber content of the product, thereby enhancing its benefits. The purpose of this study was to determine the effect of inulin addition on the organoleptic quality, fiber content, and acceptability of yogurt. The study used a completely randomized design (CRD) with one control, three treatments, and two repetitions. The amounts of inulin added were 7.5, 10, and 12.5 grams per portion. Data were analyzed using the Kruskal-Wallis test at the 5% level. Organoleptic test results showed that the average level of panelists' preference for taste, aroma, color, and texture was highest in treatment F2, with the addition of 7.5 grams of inulin. The test results indicated that the best treatment in terms of sensory taste, aroma, color, and texture was treatment F2, with the addition of 10 grams of inulin. There was a significant effect of inulin addition on the texture and taste of yogurt (p<0.05). The acceptability of yogurt with inulin addition was 92.8%. The fiber content test revealed a fiber content of 12.78%. It can be concluded that the addition of inulin to yogurt affects the organoleptic qualities of texture and taste and increases fiber content and product acceptability. The best results were obtained with the addition of 10 grams per portion. Further research is recommended to evaluate the number of bacteria and the shelf life of yogurt with added inulin.